Cause-specific mortality in British coal workers and exposure to respirable dust and quartz. Issue 4 (9th October 2009) - Miller, Brian G; MacCalman, Laura
Abstract : Objectives: In the 1950s the Pneumoconiosis Field Research (PFR) programme was set up to study the health of British coal workers. Studies included regular health surveys, an intensive characterisation of workers' individual exposures, and entry to a cohort followed up to the present for cause-specific mortality. This study reports on analyses of cause-specific mortality in a cohort of almost 18 000 men from 10 British collieries. Methods: External analyses used standardised mortality ratios (SMRs), comparing observed mortality with reference rates from the regions in which the collieries were situated. Causes investigated include lung and stomach cancers, chronic obstructive pulmonary disease and cardiovascular endpoints. Internal analyses used Cox regression models with time-dependent exposures adjusting for the confounding effects of age, smoking, cohort entry date and regional differences in population mortality rates. Results: Several causes showed evidence of a healthy worker effect early in the follow-up, with a deficit in the SMR diminishing over time. For most of the causes there was a significant excess in the latter part of follow-up. Internal analyses found evidence of an association between increased risks of lung cancer and increased quartz exposure, particularly at a lag of 15 years. Risks of mortality from non-malignant respiratory disease showed increases with increased exposure to respirable dust. Conclusions: This paper adds to the evidence on the long-term effects of exposure to coalmine dust on mortality from respiratory diseases.